Citizenship Education in Japan - Ikeno, Norio (Continuum Studies in Educational Research, 2011)
This fascinating volume introduces an international audience to citizenship in Japan. It traces the development of citizenship education from before the Second World War to the present day, demonstrating the role of both the school system and the wider society. The book provides a detailed account anchored in critical analysis of the curriculum, educational resources, pedagogy and assessment. Citizenship Education in Japan explores controversial issues through tracing four themes: global/intercultural education environmental education geographical education historical education It also examines current curricular innovations. Overall, this insightful volume demonstrates that contemporary citizenship education entails not only knowledge about social, historical and geographical affairs, but also participation in society – locally, nationally, and globally.